Off-Record Politeness Strategies and Different Gender’s Characteristics in Woman at Point Zero Novel - Gabby Allen Vica; Hendi Pratama; Katharina Rustipa (English Education Journal, 2023)
Language is a communication tool which is used to exchange information between the speakers and the hearers according to their particular purposes. The indirect message in communication is called off record politeness; it helps the speakers avoiding responsibility of the hearers’ self image. The purposes of the study are explaining off record politeness strategies based four maxim violation. Then, explaining the characteristics of gender differentiate male and female’s off record politeness strategies. Moreover, explaining the relationship among different off record strategies and the gender. The data in this study is male and female’s utterances cointaining off record politeness. The result shows that male frequently used rthetorical questions and female mostly used metaphors strategies. The frequent male’s characteristic in communication is succint language meanwhile female’s characteristic is storytelling. The result found relationship between gender’s characteristics in the use of off record politeness strategies.